Hubungan Kekuatan Otot Lengan dan Kelincahan Terhadap Passing Bawah Bola Voli di SDN Kecamatan Ganeas - Dede Muhamad Fattah; Dinar Dinangsit; Encep Sudirjo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the relationship between arm muscle strength and volleyball underhand passing ability, the relationship between agility and underhand passing ability, and the simultaneous relationship between arm muscle strength and agility and underhand passing ability in elementary school students in Ganeas District. The focus of the study was directed at revealing the role of these two physical condition components as factors supporting basic volleyball technical skills at elementary school age. The method used in this study was a quantitative approach with a correlational design through multiple linear regression analysis. The study involved 15 students as a sample selected using a multistage sampling technique. Data collection was carried out through physical condition tests to measure arm muscle strength and agility, and skills tests to measure underhand passing ability. The data obtained were then analyzed using normality tests, linearity tests, and regression tests to determine the relationship between variables empirically. The results showed that the data were normally distributed and had a linear relationship, thus meeting the requirements for further analysis. Partially, arm muscle strength had a coefficient of 0.549 with a positive relationship, while agility had a coefficient of 0.249 which also indicated a positive relationship to underhand passing ability. However, both variables did not show a statistically significant effect because their respective significance values ​​were greater than 0.05, namely 0.125 for arm muscle strength and 0.372 for agility. The conclusion of this study is that arm muscle strength and agility have a tendency to have a positive relationship with volleyball underhand passing ability in elementary school students, but have not yet provided a statistically significant effect. Keywords : Volleyball, Arm Muscle Strength, Agility, Underhand Passing